2019
DOI: 10.1093/deafed/enz031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gesture and Linguistic Experience on Sign Perception

Abstract: In the past years, there has been a significant increase in the number of people learning sign languages. For hearing second language (L2) signers, acquiring a sign language involves acquiring a new language in a different modality. Exploring how L2 sign perception is accomplished and how newly learned categories are created is the aim of the present study. In particular, we investigated handshape perception by means of two tasks, identification and discrimination. In two experiments, we compared groups of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Knowledge of which properties are similar between sign and oral languages (i.e., modality‐independent) and which properties are determined by the language modality (i.e., modality‐dependent) is required for exploring the coupling between linguistic and indexical information in sign languages. At the linguistic level, accumulated evidence has indicated that sign and oral languages are sensitive to the same linguistic phenomena, including lexical frequency (Emmorey et al., 2013; Jescheniak & Levelt, 1994) and categorical perception (Gimeno‐Martínez et al., 2020; Kuhl, 2004). This implies that linguistic information is organized and flows across levels of processing (e.g., semantic, lexical, and phonological) similarly in both modalities.…”
Section: Background Literaturementioning
confidence: 99%
“…Knowledge of which properties are similar between sign and oral languages (i.e., modality‐independent) and which properties are determined by the language modality (i.e., modality‐dependent) is required for exploring the coupling between linguistic and indexical information in sign languages. At the linguistic level, accumulated evidence has indicated that sign and oral languages are sensitive to the same linguistic phenomena, including lexical frequency (Emmorey et al., 2013; Jescheniak & Levelt, 1994) and categorical perception (Gimeno‐Martínez et al., 2020; Kuhl, 2004). This implies that linguistic information is organized and flows across levels of processing (e.g., semantic, lexical, and phonological) similarly in both modalities.…”
Section: Background Literaturementioning
confidence: 99%
“…Sign language users show differences in low level motion perception (Bosworth, Petrich & Dobkins, 2013), perception of sign-related body movements (Poizner, 1983) or positioning (Almeida, Poeppel, & Corina, 2016), visual attention, and the spatial maps of where visual attention is allocated in the focal region and/or periphery of the visual field (Dye, Baril, & Bavelier, 2007; Stoll & Dye, 2019). Signers may also show greater sensitivity to observed handshapes (Baker, Idsardi, Golinkoff, & Petitto, 2005; Morford, Grieve-Smith, MacFarlane, Staley, & Waters, 2008) although there are contradictory findings in this area (Gimeno-Martínez, Costa, & Baus, 2019). Overall, accumulating evidence shows that people with extensive sign language expertise exhibit differences in perception, but the full extent and nature of these differences is yet to be understood.…”
Section: Neural Correlates Of Sign Language Perception and Productionmentioning
confidence: 99%